What Determinants Make Internship Intention to Join the Hospitality Industry - Annas, Mohammad; Humairoh; Nosica Rizkalla; Margareta Priswati Hayu Pratiwi (Dinasti Publisher, 2023)
Retaining the program from the campus so that you can enjoy for the first time the way to practice in work, which may be referred to as internship work, offers college students an idea of running in the industry. Within internships performed by college students, there are numerous factors to attain satisfaction in an internship, one among which is the element of social support within the painting's surroundings. Consequently, this examination discusses the influence of social assistance on internship pleasure which affects the goal of signing up for the hospitality industry of college students who carry out internships in 4-stars hotels. This research uses quantitative techniques and judgemental sampling techniques. Primary data collection is information collected by distributing questionnaires to students of private universities in the Jakarta and Banten areas who did internships at four-star hotels within the Jakarta and Banten regions. The data amassed became 183 respondents. The data obtained is processed using the Structural Equation Modeling (SEM) method. The outcomes showed that perceived supervisor support and coworker support positively impacted Internship satisfaction, and perceived organizational support did not affect Internship satisfaction. Internship satisfaction impacts the intention to join the hospitality industry.